Feminismo e empoderamento : discursos contra-hegemônicos nas propagandas de cosméticos para mulheres - Ribeiro, Érika Ramos (2018)
The female figure has historically been (and still is) considered submissive to man, with male supremacy as a social characteristic in society. However, through feminist movements, which began in the nineteenth century but had greater support since the twentieth century, there was a contribution to the emancipation and evolution of women as public citizens, modifying their role and economic and political condition. In a new social configuration, women can not be seen only under the mother and housewife approach. The modern woman seeks rights and empowerment, a term that can be understood as a notion of people guiding their own lives, making their choices, taking control of their destinies. Advertising, a fundamental aspect in social relations of power, seeks to follow this path of the feminine image, building through the advertisements a discourse based on several other discourses, knowledge, beliefs and practices, which provide guidance, advice and impositions, it becomes a mirror of society that reflects and reaffirms the current logic. Considering all the discussion about the social problematic of the behavior of women, in their condition of inferiority under masculine domination, and the relation of this representation in the publicity, this work seeks to analyze anti-hegemonic discourses present in three advertisements of cosmetics for women : two from the year 2016, from the companies Avon and Quem said, Berenice ?, and another, from 2017, from the cosmetics company Natura, which make up the corpora of this research. The objective is to prove the existence of an attempt to re-represent women between advertising and society, that is, to understand the way in which the female being is portrayed from the perspective of the media. The analysis of the French Line Discourse, based on Michel Pêcheux (1988, 1997, 2008), and other theoretical references, such as Helena Brandão (2009), Eni Orlandi (1995, 2000), Raymond Williams (1973, 2011), Stuart Hall (2003), Branca Moreira Alves and Jacqueline Pintaguy (1891) and Céli Regina Jardim Pinto (2004). The results evidenced that the discourses of the three advertisements analyzed in this research can not represent female counter-hegemonic figures, but they use elements that subvert hegemony, which shows the beginning of an important trajectory for the woman and her history.